Properties of artisanal cheese made from dairy cows fed tropical grasses and commercial feed - Mecias Moreira, Luis Fernando (2022)
The objective of this work was to determine the properties of artisan cheese, which was made from dairy cows fed with tropical grasses Brachiaria decumbens; Panicum maximum as the sole source of isocaloric food based on a commercial concentrate. It was possible to determine that the milk yield by the cows was between 10.57 and 11.73 kg cow day-1. Subsequently, cheese was made from each of the treatments; Then, an analysis of the product was carried out, which was determined that it meets the quality criteria of both chemical composition and sanitary hygiene contemplated in the Technical Regulation NTE INEN 1528; Regarding the percentage of yield, we have that it was slightly low between 3.52 and 3.91 while the indicators of technological efficiency regarding the use of casein 51.74 to 52.84% and use of fat 32.99 34.68%; This qualifies the product as a fresh cheese that still generates whey, which is why the milk components are not used in a good way.